DISTANCE EDUCATION IN SOCIAL WORK: CHALLENGES AND LIMITS OF TRAINING AT A PRIVATE IES IN MANAUS (Editora Impacto Científico, 2025)
This study addresses the professional training in Social Work in Manaus through the Distance Education (EaD) modality. The general objective was to analyze the Social Work training in the EaD format at a private higher education institution in Manaus, Amazonas. The specific objectives were: to identify the profile of Social Work students in EaD programs in Manaus and in the interior regions of Amazonas where the course is offered; to identify the challenges faced by students in the EaD modality; and to understand the strategies used to overcome these challenges. The research adopted a critical perspective for data analysis and was carried out through documentary and field research, with questionnaires applied to the participants. The results showed that most students feel prepared to work as social workers after completing the course, although some still report insecurities, highlighting the need to strengthen practical aspects of the training. Regarding the quality of education, many believe that the EaD course offers the same quality as the in-person modality, while others note differences, indicating the need for improvements. The identified strategies include time management, the use of additional study materials, and peer support, reinforcing the importance of planning and collaboration in the EaD context. The main challenges identified include weak tutor support and a lack of in-person guidance, especially during internships and the writing of the final thesis (TCC).